Kajian Faktor Ketersediaan SDM, Ketersediaan Material, Cuaca serta Anggaran dan Dukungan Kebijakan Pemerintah dalam Pembangunan Jalan Kabupaten Kolaka Utara - Thasman, Thasman; Ahmad, Sitti Nurjannah; Soeparyanto, Try Sugiyarto (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2026)
Road construction in North Kolaka Regency is a strategic effort to improve regional connectivity and encourage regional economic growth. This study aims to analyze factors that influence the implementation of road construction, including the availability of human resources (HR), the availability of construction materials, weather conditions, as well as budget and government policy support. The study method uses a descriptive-analytical approach by reviewing field data, planning documents, and related regulations. The results of the study indicate that the availability of human resources, materials and equipment, weather and geographical conditions, as well as budget and government policy support, both partially and significantly have a positive and significant influence on the implementation of road construction in North Kolaka Regency, especially on the Simbula - Watunohu road section.